Negative Campaigning across Different Communication Channels: Different Ball Games? - Walter, Annemarie S. and Vliegenthart, Rens (The International Journal of Press/Politics, 2010)
In this article, the authors address the question of to what extent negative political campaigning differs when looking at different communication channels. They compare paid publicity, election debates, and newspaper coverage for the 2006 Dutch parliamentary elections and conduct an elaborate content analysis. Results show that the level of negative campaigning does not differ greatly across these channels, although election debates clearly show the highest amount of this type of campaigning. Notably, negative campaigning takes a different form in newspaper coverage, where appeals are more personal, focusing on character traits as opposed to being directed to political parties and dealing with political issues. The authors explain those results by pointing to the different levels of control politicians exert over communication channels. They also make a plea to other researchers investigating negative campaigning, asking them to fully consider that their results might be seriously biased by the communication channel they investigate.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xOTQwMTYxMjEwMzc0MTIy